An attempt to improve bovine Mycoplasmatales primary isolation - Liberal, Maira Halfen Teixeira; Boughton, Ernest (Pesquisa Agropecuaria Brasileira, 1994)
The sensitivity to 30 antibiotics of Mycoplasma (10 strains) and Acholeplasma (8 strains) was tested in an attempt to find a better one for suppression of contamination in the culture media, used for primary isolation of Mycoplasmatales. The most effective antibiotics for suppression of Gram-positive and Gram-negative organisms and did not inhibit Mycoplasmatales were: carbenicillin, vancomycin and fosfomycin. Although none of the antibacterial drugs that are inhibitors of cell wall synthesis was active against Mycoplasmatales, the majority of them were also ineffective against Gram-positive and/or Gram-negative contaminant bacteria.